ANALYSIS OF THE VISIONARY LEADERSHIP OF THE PRINCIPAL IN IMPROVING TEACHER PERFORMANCE - Zuhro, Siti Li’anatuz; Rindaningsih, Ida (Journal of Social Science, 2025)
Objective: This study examines the impact of visionary leadership on teacher performance in educational institutions, emphasizing the principal's role in adapting to educational changes while advancing institutional goals. The research aims to determine how the implementation of visionary leadership by school principals enhances teacher performance and contributes to the success of educational outcomes. Method: A Systematic Literature Review (SLR) approach was employed, synthesizing and evaluating existing studies to identify patterns and insights regarding the relationship between visionary leadership and teacher performance. Results: The findings reveal that principals who implement visionary leadership foster a conducive environment for innovation and motivation among teachers, which significantly improves their performance and aligns efforts with institutional visions and missions. Such leadership practices enhance collaboration, professional development, and the overall quality of education. Novelty: This study underscores the critical role of visionary leadership in bridging the gap between institutional vision and teacher performance, providing a comprehensive synthesis of its impact on educational success. These findings contribute to the limited research on leadership styles in education, emphasizing the importance of strategic leadership in driving institutional excellence.